2000
DOI: 10.3141/1703-11
|View full text |Cite
|
Sign up to set email alerts
|

Use of Public Transportation by Airport Passengers

Abstract: Transportation plans in some communities have focused on providing rail service to the local airport, whereas other communities have emphasized bus and van service. The opportunity for rail, bus, and van service at U.S. airports and the use of these services by airline passengers at the large airports in the United States and overseas are reviewed. On the basis of the airline passenger mode share data presented, there appears to be a “ceiling” on the market for public transportation (rail, bus, and shared-ride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…Very low market share of public transport in US (10-15%) was also pointed out by Mandle at al. [3]. On the contrary, in Asia the results were quite different as public transport accounts for over 60% of airport ground access market [3].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Very low market share of public transport in US (10-15%) was also pointed out by Mandle at al. [3]. On the contrary, in Asia the results were quite different as public transport accounts for over 60% of airport ground access market [3].…”
Section: Literature Reviewmentioning
confidence: 97%
“…They found that less than 8% of the departing air travelers accessed Midway and O'Hare airports. Mandle et al (2000) concluded that 10% to 15% is the maximum market share of public transport at airports in the United States. Sobienaik, et al (1979) studied the access mode choice at Ottawa-Hull and vicinity in Canada and found that walking time and luggage handling are the significant variables for mode choice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fewer than 10% of airport passengers travel to or from Hartsfield Jackson by transit. Use of transit for airport travel is associated with the ability to walk to transit at the trip's origin or destination, and may suggest an untapped niche for shuttle and van services (Mandle, Mansel, and Coogan, 2000). Humphreys and Ison (2005)…”
Section: Airport Areasmentioning
confidence: 99%